Comparative Transcriptome Analysis Reveals Differential Regulation of Flavonoids Biosynthesis Between Kernels of Two Pecan Cultivars - Zhang, Chengcai; Ren, Huadong; Yao, Xiaohua; Wang, Kailiang; Chang, Jun (Frontiers in Plant Science, 2022)
Flavonoids influence the flavor and nutritional value of pecan nuts. However, limited information is available regarding the molecular mechanisms underlying pecan flavonoid biosynthesis. Here, we used a high (‘YLC28’) and a low (‘Oconee’) flavonoid content cultivar as the research objects. The changes in flavonoid content and the gene transcription patterns during kernel development were identified. Different accumulation patterns of total flavonoids (TF) and condensed tannins (CT) were observed between the two cultivars. The contents of TF and CT in ‘YLC28’ were 1.76- and 2.67-fold higher levels than that of ‘Oconee’ on 150 days after full bloom of female flowers, respectively. In total, 30 RNA-Seq libraries were constructed and sequenced. The upregulated genes in ‘YLC28’ were highly enriched in flavonoid-related pathways. Thirty-three structural genes were identified, and the expression of two phenylalanine ammonia lyases, one chalcone synthase, one flavonoid 3′,5′-hydroxylase, and one flavonol synthase exhibited high correlation (r ≥ 0.7, p < 0.01) with the condensed tannin content in ‘YLC28’. A putative MYB transcription factor, CIL1093S0100, might act as a flavonoid biosynthesis repressor during kernel development. Altogether, these results will be useful for uncovering the molecular mechanisms of flavonoid biosynthesis and subsequently accelerating quality pecan breeding.